Initial Experience of Appendicular Fracture Fixation with Low Profile Titanium Alloy Locking Plates: A Retrospective Study of 30 Fractures - Treharne, David Rhys; Rutherford, Scott (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
This retrospective study assessed the complications and mid-term outcomes of osteosynthesis using the String of Pearls Low Profile (SOP-LP) plate system in cats and small dogs with appendicular fractures.Clinical data from April 2018 to June 2021, involving 30 fractures in 29 cases, were reviewed. Fractures were stabilized using either the 1.5-mm or 2.0-mm SOP-LP plate. Data included patient signalment, fracture description, repair method, intraoperative complications and short-term follow-up outcomes. Midterm follow-up was performed by telephone-based veterinary questionnaires.Of the 30 fractures, 3 had complications linked to the SOP-LP system. Overall, 7/30 had complications. Major complications (n = 6) included two implant failures, one implant-associated irritation and three Kirschner wire migrations. Implant failures (n = 2) were with the 1.5-mm plates stabilizing radius/ulna fractures in dogs weighing over 2.9 kg. Short-term radiographic follow-up demonstrated clinical or radiographic union in all cases. In all cases available (n = 18) for midterm follow-up, the function was found to be full or acceptable.The SOP-LP plate can be used successfully for a wide variety of fractures in cats and small dogs; however, careful case selection is required, particularly when using the 1.5-mm plate as a single implant in patients weighing over 3 kg.
Keywords: fracture repair systems; locking plates; orthopaedic surgery